Five-year follow-up of a woman with pregnancy and lactation-associated osteoporosis and vertebral fractures - Sato Y; Uzawa M; Matsumoto H; Iwamoto J (Dove Medical Press, 2012)
Jun Iwamoto1, Yoshihiro Sato2, Mitsuyoshi Uzawa3, Hideo Matsumoto11Institute for Integrated Sports Medicine, Keio University School of Medicine, 2Department of Neurology, Mitate Hospital, Fukuoka, 3Department of Orthopaedic Surgery, Keiyu Orthopaedic Hospital, Gunma, JapanAbstract: We report the 5-year follow-up of a young woman who developed vertebral fractures after pregnancy and lactation and was treated with active vitamin D hormone. A 32-year-old Japanese woman consulted us because of acute lower back pain caused by L2 and L5 vertebral fractures after pregnancy and lactation. Following cessation of breast-feeding, analgesia, bed rest, and wearing of a hard brace, her lower back pain disappeared within 2 months. After 5 years of treatment with alfacalcidol 1 µg daily, the lumbar spine (L1, L3, L4) bone mineral density increased by 21.4% following vigorous reductions in bone turnover markers. No osteoporotic fractures occurred, and the vertebral fractures healed. The patient experienced no side effects, including hypercalcemia. Thus, the present case report shows long-term changes in bone turnover markers and lumbar spine bone mineral density, as well as long-term safety of alfacalcidol treatment in a young woman with pregnancy and lactation-associated osteoporosis and vertebral fractures.Keywords: young woman, pregnancy, alfacalcidol, bone mineral density, osteoporosis, vertebral fracture